The impact of corporate governance on earnings management in Korea / Hyo Jin Kim and Soon Suk Yoon - Kim, Hyo Jin; Yoon, Soon Suk (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
The purpose of this study is to analyze whether an improvement in corporate governance can mitigate earnings management. Our study further investigates corporate governance factors that mitigate the earnings management practices. of 2004 and 2005. The degree of earnings management is measured by discretionary accruals and total accruals. We use mean difference tests and regression analyses to investigate the impact of corporate governance on earnings management. The main variables of interest in our study are the activities of outside directors in board meetings, the establishment of an audit committee, concentrated ownership and foreign ownership. We find that the independence of the board of directors, ownership concentration, foreign ownership, leverage ratio and firm size significantly affect discretionary accruals and total accruals. In sum, our results partially support the hypothesis that corporate governance and earnings management are significantly related. However, we find that the adoption of an audit committee does not significantly affect the degree of accruals.